Detailed analyses of fresh and dried maqui (Aristotelia chilensis (Mol.) Stuntz) berries and juice. (1st January 2016) - Brauch, J.E.; Buchweitz, M.; Schweiggert, R.M.; Carle, R.
Highlights: Drying and juice production substantially affected the stability of maqui anthocyanins. Stability of cyanidin and delphinidin derivatives differed during processing. Maqui pomace was a valuable source for obtaining polyunsaturated fruit oils. Maqui products exhibited nutritionally relevant mineral and trace element levels. Maqui berries represent an extremely pigment-rich "superfruit". Abstract: In this study, a detailed chemical characterization of nutritionally-relevant, quality-determining constituents in dried and fresh fruits as well as juices of maqui ( Aristotelia chilensis (Mol.) Stuntz) is provided. A total of 8 glycosylated anthocyanins was characterized in maqui fruits, being composed of differently substituted cyanidin and delphinidin derivatives. During processing into juice, a substantial loss in total anthocyanin contents (TAC) was observed. TAC values were also reduced after drying of maqui berries. Likewise, the browning index (BI) of fresh fruits increased during processing. Being composed of flavonol glycosides and ellagic acids, 17 non-anthocyanin phenolics were characterized in all maqui samples. Besides characterizing phenolic compounds, antioxidant activities, total phenolics, major sugars, non-volatile organic acids, minerals and trace elements were quantitated. Moreover, total lipid contents and the fruits' mainly unsaturated fatty acid profiles are reported. The presented results indicate the high potential of maqui as so far under-utilized but extremely pigment-rich "superfruit".